Strategi Penguatan Kapasitas Kelitbangan di Provinsi Sumatera Barat - Afriyanni; Fitri, Suci; Pranasari, Melati; Manoby, Worry Mambusy (Jurnal Bina Praja, 2021)
The government places research and development (R & D) to take a significant role in implementing local government in an agency. However, there are still many regional research and development tools joined by the Regional Development Planning Agency (Bappeda). This research is qualitative research that aims to describe the conditions and problems of regional research and development joined by the Regional Development Planning Agency (Bappeda) and the strengthening strategy and role of regional research and development tools in planning dominance. Primary data were collected through online surveys and in-depth interviews and secondary data through the study of documentation and related statutory regulations. Data analysis was carried out descriptively. The results showed that the regional research and development under the Regional Development Planning Agency (Bappeda) still face internal and external obstacles. Their roles and functions are not optimal. This study recommends strategies for strengthening regional research and development and mechanisms for synergizing the roles of research, development, and planning.